2020
DOI: 10.1038/s41598-020-75078-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of gamma-glutamyl transferase with subclinical coronary atherosclerosis and cardiac outcomes in non-alcoholics

Abstract: In an asymptomatic population, we determined the relationship between serum gamma-glutamyl transferase (GGT) and subclinical atherosclerosis, using coronary computed tomography angiography (CCTA). This was a retrospective observational cohort study which analyzed 5120 consecutive asymptomatic individuals with no prior history of coronary artery disease or significant alcohol intake who voluntarily underwent CCTA as part of a general health examination. All subjects were stratified into tertiles based on GGT le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
2
2
0
Order By: Relevance
“…Age, PDW, MPV, SUA, and GGT were observed as independent risk factors for SCAS, consistent with previous studies ( 29 33 ). Inflammation-related markers such as WBC, BASO, and LYC, were also found to be independent risk factors for SCAS.…”
Section: Discussionsupporting
confidence: 92%
“…Age, PDW, MPV, SUA, and GGT were observed as independent risk factors for SCAS, consistent with previous studies ( 29 33 ). Inflammation-related markers such as WBC, BASO, and LYC, were also found to be independent risk factors for SCAS.…”
Section: Discussionsupporting
confidence: 92%
“…In the first approach, upregulation of GGT1 was identified as a common marker of LEAD, AAA and CVD subjects after comparison to healthy controls (Figure 1). This finding is in concordance with previous studies, where increased serum level of GGT was found to be associated with peripheral arterial disease (PAD) in non-alcoholic males [47] and with higher risk of subclinical coronary atherosclerosis, coronary artery calcification and cardiac events [48,49]. Elevated serum GGT levels are related to increased concentrations of homocysteine [50], which is well known independent risk factor of cardiovascular diseases, including LEAD [51].…”
Section: Discussionsupporting
confidence: 92%
“…Considerable evidence from epidemiolocal studies support the positive correlation of GGT with the degree of coronary atherosclerosis and incident CVD risk 8 , 17 . In addition, high GGT was associated with high-risk features of atherosclerosis detected by coronary computed tomography and with poorer cardiac outcomes defined as a composite of all-cause death, myocardial infarction, unstable angina requiring hospitalization, or coronary revascularization in subjects without significant alcohol consumption 18 . Similarly, GGT was positively associated with the risk of incident heart failure in prospective cohort studies 19 , 20 and was an independent predictor of death or heart transplantation in patients with heart failure 21 .…”
Section: Discussionmentioning
confidence: 99%